2023
DOI: 10.1038/s41467-022-35774-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation and degradation of strongly reducing cyanoarene-based radical anions towards efficient radical anion-mediated photoredox catalysis

Abstract: Cyanoarene-based photocatalysts (PCs) have attracted significant interest owing to their superior catalytic performance for radical anion mediated photoredox catalysis. However, the factors affecting the formation and degradation of cyanoarene-based PC radical anion (PC•‒) are still insufficiently understood. Herein, we therefore investigate the formation and degradation of cyanoarene-based PC•‒ under widely-used photoredox-mediated reaction conditions. By screening various cyanoarene-based PCs, we elucidate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 79 publications
3
45
0
Order By: Relevance
“…From a fundamental standpoint, the PET-RAFT method can be regarded as an extension of the conventional RAFT procedure. Because PET-RAFT uses a photocatalyst (PC) as an energy and/or electron transfer source for radical generation, it does not require an external initiator and heat as an energy source to drive polymerization. , ,, In contrast to conventional radical initiators, PCs exhibit great diversity in their materials and structures, making it possible to tailor their properties to a wide variety of conditions. ,,,, This implies that the successful polymerization of a variety of monomers under the desired reaction conditions could be achieved using the proper PC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a fundamental standpoint, the PET-RAFT method can be regarded as an extension of the conventional RAFT procedure. Because PET-RAFT uses a photocatalyst (PC) as an energy and/or electron transfer source for radical generation, it does not require an external initiator and heat as an energy source to drive polymerization. , ,, In contrast to conventional radical initiators, PCs exhibit great diversity in their materials and structures, making it possible to tailor their properties to a wide variety of conditions. ,,,, This implies that the successful polymerization of a variety of monomers under the desired reaction conditions could be achieved using the proper PC.…”
Section: Introductionmentioning
confidence: 99%
“…2,[10][11][12][13]20,21 In contrast to conventional radical initiators, PCs exhibit great diversity in their materials and structures, making it possible to tailor their properties to a wide variety of conditions. 2,13,20,22,23 This implies that the successful polymerization of a variety of monomers under the desired reaction conditions could be achieved using the proper PC. Recently, concerns regarding the life cycle of polymers, including raw materials for polymer production, energy sources, and end-of-life treatment, have been growing as a result of current global environmental issues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…48 The produced long-lived triplet excited states facilitate the electron transfer process. Thus, the superior catalytic performance of 4CzIPN 57,58,61,62 and PC1 was most probably attributed to the sufficient negative E ox * and the long-lived triplet CT excited states. Herein, we propose the OPC design strategy of twisted link between strong electron-donating (D) unit and weak electron-withdrawing (A) unit.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The photoluminescence lifetimes were 1.40, 1.34, and 5.78 ns for PC1-3, respectively. 4CzIPN exhibited a long photoluminescence lifetime of 240.7 ns in DMF due to the efficient generation of triplet excited states and thermally activated delayed fluorescence (TADF) property. ,,, The lifetime of metal–ligand charge transfer (MLCT) triplet state Ir­(ppy) 3 was 76.1 ns in DMF. The photoluminescence lifetime of perylene was 6.5 ns.…”
Section: Resultsmentioning
confidence: 99%
“…Additional control experiments revealed that both thiol and light remained necessary reaction components (see SI for details). Taken together, these data suggest that CO 2 •– addition into unactivated alkenes is slower than photocatalyst decomposition, which potentially occurs via radical attack on the isophthalonitrile core. In contrast, we suspect that CO 2 •– addition into activated alkenes (e.g., vinylarenes) outcompetes this pathway given that the dye was necessary under those conditions and that no catalyst bleaching was observed…”
mentioning
confidence: 99%